Google Ads Optimization as a Digital Marketing Strategy in Increasing the Competitiveness of Fashion MSMEs - Ikhsan Nendi; Abdullah Abdullah; Arif Maulana (Publikasi Indonesia, 2025)
This research aims to develop and validate the Google Ads Optimization Framework for Fashion SMEs (GAOF-FS) as a strategic solution to increase the competitiveness of fashion MSMEs in the digital era. Using a Design Science Research approach with a mixed-method method, this research involved 30 fashion MSMEs in Cirebon through surveys, in-depth interviews, and Focus Group Discussions. The results of the analysis showed that 67.3% of MSMEs experienced limited digital knowledge, 72.8% were constrained by budget, and 81.5% had digital positioning difficulties. Only 3.3% of MSMEs are actively using Google Ads. The GAOF-FS framework developed consists of four integrated modules: (1) Strategic Planning Module with components of ecosystem analysis, competitor mapping, and campaign objective determination; (2) The Campaign Design Module includes a keyword research framework, ad copywriting template, and landing page optimization; (3) Budget Management Module with dynamic allocation model and ROI calculator; (4) Performance Monitoring Module with dashboard analytics and GAPS metrics. Expert validation shows an approval rate of 87.5% for relevance, 85.0% for technical feasibility, 90.0% for user-friendliness, and 88.8% for potential impact. User validation (MSMEs) resulted in a usability score of 4.23/5, perceived usefulness 4.47/5, ease of use 4.15/5, and intention to use 4.38/5. This framework provides academic contributions in the form of adaptive models based on local contexts and practical contributions in the form of operational guidelines that are applicable to MSMEs with limited digital literacy.